Prostacyclin prevents nitric oxide-induced megakaryocyte apoptosis - Pozner, Roberto Gabriel (2005)
1. We have previously demonstrated that nitric oxide (NO) triggers CD34⁺-derived megakaryocyte apoptosis. We here show that prostacyclin (PGI₂) inhibits PAPA/NO-induced megakaryocyte death detected by fluorescent microscopy and flow cytometry. 2. The cAMP-specific phosphodiesterase inhibitor, Ro 20-1724, and the permeable analog dibutyryl-cAMP also delayed apoptosis. PGI₂ effect was fully prevented when adenylyl cyclase activity was suppressed by SQ 22536, and partially reversed by the permeable protein kinase A inhibitor PKI 14-22 amide. ELISA showed that while both PGI₂ and NO alone or synergistically raised cAMP, only NO was able to increase intracellular cGMP levels. 3. Treatment of megakaryocytes with PGI₂ abolished both basal and NO-raised cGMP levels. Addition of 8-pCPT-cGMP or activation of soluble guanylyl cyclase by BAY 41-2272 induced cell death in a concentration-dependent manner, and ODQ, an inhibitor of guanylyl cyclase, prevented both PAPA/NO- or BAY 41-2272-induced apoptosis. Specific cGMP phosphodiesterase inhibition by Zaprinast or suppression of adenylyl cyclase by SQ 22536 enhanced the PAPA/NO proapoptotic effect. 4. PGI₂ completely inhibited NO-mediated generation and the increased activity of the cleaved form of caspase-3. 5. In conclusion, our results demonstrate that contrary to their well-known direct and synergistic inhibitory effects on platelets, PGI₂ and NO regulate opposite megakaryocyte survival responses through a delicate balance between intracellular cyclic nucleotide levels and caspase-3 activity control.